Annals of the Missouri Botanical Garden - Henry Shaw School of Botany. Graduate Laboratory; Henry Shaw School of Botany; Missouri Botanical Garden (Rumford Press, 1914)
Contains scientific contributions from the Missouri Botanical Garden and, from 1914-39, the Graduate Laboratory of the Henry Shaw School of Botany of Washington University; and, from 1940-1965, the Henry Shaw School of Botany of Washington University.
Keywords: Botany : Periodicals; Plants : Classification : Periodicals; Plantes : Périodiques; Plantes : Classification : Périodiques; Plantes tropicales : Périodiques; Plantes tropicales : Classification : Périodiques; Botany; Plants : Classification